Comparative Effects of Photobiomodulation and Platelet‐Rich Plasma on Joint Repair in Rats With Knee Osteoarthritis - Anne Missrie; Gabriela Saab Sampaio; Vitória Gonzaga Acerbi; Fernando Anselmo; Ítalo Ribeiro Lemes; Ana Laura Martins de Andrade (Lasers in Surgery and Medicine, 2026)
ABSTRACT Objective This study aimed to evaluate whether the combination of photobiomodulation and platelet‐rich plasma therapy provides superior anti‐inflammatory and joint‐protective effects compared to individual treatments in an experimental model of osteoarthritis. Methods Eighteen male Wistar rats were divided into three groups: Control, Photobiomodulation, and Photobiomodulation combined with Platelet‐Rich Plasma. Osteoarthritis was induced through two intra‐articular injections of methylated bovine serum albumin, administered 7 days apart. Treatments began 3 days after the second injection. Photobiomodulation was applied three times per week using an infrared laser (808 nm, 100 mW, 4 J total energy at two knee joint points). The combined therapy group received a single injection of platelet‐rich plasma in addition to photobiomodulation. The experiment lasted 21 days after osteoarthritis induction. Animals were then euthanized, and knee joint tissues were collected for histological analysis. Joint diameter was measured before induction, 3 days after induction, and at the end of the study. Results All groups showed a reduction in joint swelling by the end of the experiment; however, the Control group maintained significantly larger joint diameters, indicating greater inflammation. Histological evaluations confirmed these findings: the Control group showed severe cartilage degeneration, the Photobiomodulation group had moderate damage, and the combined treatment group displayed the best preservation of cartilage structure, resembling healthy tissue. Conclusion Isolated photobiomodulation effectively reduced in rats joint edema and inflammation progression, while its combination with Platelet‐Rich Plasma showed enhanced cartilage preservation in an experimental osteoarthritis model.